2013
DOI: 10.1007/s10903-013-9785-9
|View full text |Cite
|
Sign up to set email alerts
|

The Oral Health Status of Recent Immigrants and Refugees in Nova Scotia, Canada

Abstract: There are no published reports on the oral health status of adult immigrants and refugees in Canada. An oral health interview and clinical oral examination were conducted on 45 recent immigrants and 41 recent Bhutanese refugees, aged 18-67, in Nova Scotia, Canada. Over half (53%) of the immigrants and 85% of the refugees had untreated decay. Most (89% of immigrants; 98% of refugees) had moderate to severe gingivitis and the majority (73% of immigrants; 85% of refugees) had moderate to severe periodontitis. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 18 publications
5
48
0
4
Order By: Relevance
“…The most frequent underlying reasons for the patients' complaints are caries, poor oral hygiene, and periodontal illness. This finding converges with other studies in western countries [26][27][28].…”
Section: Discussionsupporting
confidence: 92%
“…The most frequent underlying reasons for the patients' complaints are caries, poor oral hygiene, and periodontal illness. This finding converges with other studies in western countries [26][27][28].…”
Section: Discussionsupporting
confidence: 92%
“…The OHS of older migrants was commonly found to be worse than that of older persons born in the host country. 3,[10][11][12][13][14][15][16] In a 2016 Swedish study, the proportion of edentulous individuals was found to be higher for older migrants than in the population as a whole. 11 Australian studies reported that Vietnamese, 17 Chinese, 18 Greek and Italian 19 older migrants had a higher prevalence of gingivitis.…”
Section: Oral Health Status Of Cald Older Migrantsmentioning
confidence: 99%
“…A survey of Syrian refugees in Jordan revealed that 40% of the respondents reported need for dental services [5], and in a refugee camp in Brussels, dental caries was the second most common primary diagnosis [6]. Prior American and Australian research indicated considerably higher dental treatment needs in newly arrived refugees compared to the general population [7][8][9]. Conclusions from these studies suggested an urgent need for the inclusion of refugees in targeted dental services, and resettlement programmes should include dental screening, treatment and oral health education to prevent a further decline in dental health status [8][9].…”
Section: Introductionmentioning
confidence: 99%